Correlation between RNA N6-methyladenosine and ferroptosis in cancer: current status and prospects - Liu, Qianzi; Lv, Linxi; Cai, Xueding; Zhu, Jiandong; Li, Jifa; Yang, Lehe; Xie, Xiaona; Zhao, Chengguang; Zhao, Haiyang (Frontiers in Cell and Developmental Biology, 2024)
N6-methyladenosine (m6A) is the most abundant chemical modification in eukaryotic cells. It is a post-transcriptional modification of mRNA, a dynamic reversible process catalyzed by methyltransferase, demethylase, and binding proteins. Ferroptosis, a unique iron-dependent cell death, is regulated by various cell metabolic events, including many disease-related signaling pathways. And different ferroptosis inducers or inhibitors have been identified that can induce or inhibit the onset of ferroptosis through various targets and mechanisms. They have potential clinical value in the treatment of diverse diseases. Until now, it has been shown that in several cancer diseases m6A can be involved in the regulation of ferroptosis, which can impact subsequent treatment. This paper focuses on the concept, function, and biological role of m6A methylation modification and the interaction between m6A and ferroptosis, to provide new therapeutic strategies for treating malignant diseases and protecting the organism by targeting m6A to regulate ferroptosis.